Assay of nitrification potentials in sewage sludge - Jöngren, Caroline (2016)
Sewage sludge (SS) contains valuable plant nutrients applicable to soil as fertilizer. Application to arable land is though controversial as SS can contain contains such as human pathogens, heavy metals and xenobiotics. Post-treatment processes of SS such as long term storage which can reduce pathogenic bacteria before application to soil implicate a risk of nitrogen (N) losses via emissions of the greenhouse gas nitrous oxide (N2O) and leaching of nitrate (NO3-). Nitrification is the microbial process that contributes to the turnover of these nitrogen compounds, however measurement of nitrification in long-term stored SS has never been done before. The hypothesis of nitrification activity in stored SS was the underlying reason for the questions: Is there any measurable nitrification activity in stored SS and how does it affect N2O emissions? How does different sanitation-treatments affect the nitrification in stored SS? Hence, the objective of this study was to develop an assay for assessment of potential ammonium oxidation rate (PAO) in SS, i.e. the turnover rate of ammonium oxidizing bacteria (AOB) constituting the first step in nitrification assayed in an optimal environment. Another objective was to measure the PAO in fresh and stored SS with different sanitation-treatments, and in soil after SS application. Also, by literature study evaluating the PAO in stored SS and its contribution to N2O emissions. Fresh dewatered and stored SS from the wastewater treatment plant Kungsängsverket in Uppsala was used in the development of the new PAO assay. The development was based upon the existing PAO method developed for soil. In the PAO assay a slurry (a sample with liquid substrate) is incubated during standardized conditions from which samples are taken over a time period. The sample is analyzed for nitrite content by spectrophotometric detection, which requires samples to be extracted and centrifuged. The rate of increasing NO2- content over time is defined as PAO. The assay development involved four steps: (1) Spectrophotometric scanning of SS extracts, (2) nitrite recovery analysis (3) refinement of extraction and centrifugation, and (4) optimization of sample size for a reliable PAO. The modified PAO assay compared to that used for soil resulted in reduced sample size and centrifugation of extracts amount. This resulted in a sample size with sufficient nitrification activity and minimized coloration of the extract. Accumulation of NO2- over time was analyzed using Flow Injection Analysis and demonstrated a stable and linear process. This demonstrated a stable PAO assay and nitrification activity in stored SS. The new PAO assay was used analyzing SS from a pilot study with four different sanitation treatments in combination of storage for one year with and without cover. The result showed that long term stored thermophilically digested SS (TC) had significantly higher PAO activity than the other treatments using mesophilically digested SS, probably a result of increased access of oxygen (O2) due to a more porous texture of the thermophilically digested SS. Mesophillically digested SS treated with ammonia (MAC) showed a low PAO activity as a high concentration of ammonia indicated inhibition of nitrification. The PAO rates of TC and MAC follow the results of N2O emissions from the same treatments in a previous study and indicate that inhibition of nitrification lowers the amount of substrate available for processes driving N2O emissions. SS application to soil did not change the intrinsic PAO of the soil, however some inhibitory effect was indicated with strongest effect displayed by MAC. This study shows the PAO can be measured in SS and the developed method enables e.g. analysis of sanitation treatment effects in SS. However, further development is needed to ensure a reliable assay as the PAO activity indicated to decrease with increased sample amount, probably an inhibitor effect of increasing levels of contaminants.